DEVELOPMENT OF COMMUNITY SERVICE PRACTICES INFORMATION SYSTEM BASED ON WEB IN IIB DARMAJAYA - Slamet Aldian; Sri Karnila (Jurnal TAM (Technology Acceptance Model), 2021)
The administrative system of the Community Service Work Practice (PKPM) at IIB Darmajaya currently has several problems, namely students have to queue to register themselves to the Department by filling out the registration form, the division of participant groups is still using Microsoft Excel, the student data validation process is difficult for the committee because checking files is still manually, the process of distributing DPL (Field Supervisory Board) and determining the location of PKPM which is still not systemized properly. The purpose of this study is to build a registration information system and PKPM information online and build a PKPM information system that can assist in the activities of the academic community. Data collection methods used are interviews and observation. The system development method chosen is the Waterfall method. System design using UML (Unified Modeling Language) scenarios, use case diagrams, activity diagrams, class diagrams, and sequence diagrams. From the research results, the designed Information System can obtain and provide information about registration, group division, village division, and field supervisory board division (DPL) making it easier for students in the administrative process